Project Management Competencies in Digitalization Era: Evidence from Serbian Manufacturing Industry - Stojanović Aleksić, Vesna; Bugarčić, Marijana; Slavković, Marko (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Due to the intensification of competition and the development of new production technologies, manufacturing enterprises are required to formulate appropriate strategies and use applicable tools, machines and other work equipment. The implementation of advanced technology, which features the Fourth Industrial Revolution, provides significant improvements in the efficiency and effectiveness of production, but also, it requires new key competences and skills. Bearing in mind that project management competency is perceived as an ability to perform activities within dynamic environment that lead to the superior outcomes based on defined and accepted standards, the purpose of this paper is determining the level of knowledge and skills in applying project management activities. Using the sample of 64 manufacturing firms in Serbia, the main aim is to identify the employees’ perception of readiness to implement projects within their organizations. According to previous studies, three particular categories of project management competencies are used: technical, behavioral and contextual. The obtained results can be used by managers as guidelines for the improvement of employees’ readiness for contemporary issues and the implementation of advanced technology solutions.